Eksistensi Kearifan Lokal dalam Pengaturan Pemilihan Kepala Desa Ditinjau dari Undrip (Studi Kasus Pemilihan Kepala Desa pada Masyarakat Adat Kedepatian Semerap Kabupaten Kerinci) - Dony Yusra Pebrianto; Budi Ardianto; Taufan Dyusanda Putra (Wajah Hukum, 2021)
Internationally The United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) emphasizes respect for the local wisdom of indigenous legal communities. The selection of village heads is one of the regulatory concepts stipulated in Law No. 6 of 2014 on Villages. The selection of village heads in the concept of this law is conducted simultaneously stipulated by local regulations and the procedures are specifically regulated through government regulations as stipulated in Article 31 of Law No. 6 of 2014 on Villages. But it turns out that in practice, especially in indigenous peoples, the deability of the village head election often clashes with the arrangement of the village head election. So in this case the formulation of the problem in this writing is how the arrangement of the rights of indigenous peoples in The United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and the value and concept of local wisdom that applies in the selection of village heads in 5 (Five) Villages Semerap Kedepatian. The method used in this writing uses empirical juridical methods. And in this case it is concluded that UNDRIP regulates matters relating to individual rights as well as very specific collective rights sourced from indigenous peoples. In this case the State is obliged to protect or fulfill the rights of indigenous peoples including cultural heritage and their cultural manifestations including human resources and genetics. And in the indigenous people of kedepatian semerap Kerinci regency there is a customary provision where the prospective head of the village must get customary recommendations and be appointed from Depati and Nenek Mamak. The provision is considered contrary to the local Paraturan in relation to the election of the village head. So given the provisions of UNDRIP and the 1945 Constitution, the State is obliged to protect and maintain these customs given the positive impact that arises from it. So in this case the customary provisions should be regulated in the Regulation including also about the recognition of indigenous peoples. In addition, the community needs to open a paradigm on human rights in the selection of village heads in addition to the paradigm of the enforcement of customary law there needs to be flexibility from the State as long as it is not contrary to national law.